Unified mesoscale picture of nonlinear generation of zonal flows in toroidal geometry - Zihao Wang; Shaojie Wang (Nuclear Fusion)
Recent experimental findings on limit-cycle-oscillations indicate that the nonlinear driving of the turbulent poloidal Reynolds stress to zonal flows (ZFs) is not a significant factor in the toroidal geometry, sparking fundamental controversial issues within the fusion community. By using the global nonlinear gyrokinetic simulations, we propose a unified mesoscale picture of nonlinear driving of ZFs in the ion-temperature-gradient turbulence. ZFs are nonlinearly driven by the turbulent energy flux and the turbulent poloidal Reynolds stress. The turbulent energy flux is not shielded by the toroidal geometry effect in nonlinearly driving ZFs. The turbulent poloidal Reynolds stress is not shielded on the time scale shorter than the ion bounce period; however, on the time scale longer than the ion bounce period, the turbulent poloidal Reynolds stress is indeed shielded by the toroidal geometry effect.